Is there discretionality in the judicial decision? - García Amado, Juan Antonio (2008)
Two different sets of legal theories have denied that judges have any discretion when deciding cases. The first was the naive formalism as practiced in the 19th century in France for the Exegesis School and the Conceptual Jurisprudence School (Begriffsjurisprudenz) in Germany. On the other hand, was the sophisticated formalism of the late 20th century that integrated the right with the social ethics, both establishes a connection between law and social morality, and undertakes a moral reading of the Constitution so that positive law could offer one right answer for every case. Against all of this, the juridic positivism of the 20th century has regarded judicial discretion as a consequence, so unavoidable as unadvisable of the structure of any existing legal system.